2009
DOI: 10.1017/s1368980009005825
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a semi-quantitative FFQ for sodium intake in low-income and low-literacy Brazilian hypertensive subjects

Abstract: Objective: To assess the reliability and validity of an FFQ to evaluate dietary patterns of Na consumption among low-income and low-literacy Brazilian hypertensive subjects. Design: The initial FFQ was submitted to content analysis with the pre-test administered to fifteen subjects. Reliability was evaluated according to the reproducibility criterion, with interviewer administration of the FFQ twice within a 15 d interval. Validity was assessed against a 24 h recall (132 subjects), a 3 d diet record (121 subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0
19

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(117 citation statements)
references
References 26 publications
5
75
0
19
Order By: Relevance
“…Among the factors related to the development and progression of hypertension, the elevated consumption of salt has been directly associated with the increase in blood pressure levels and the occurrence of cardiovascular complications (2)(3)(4)(5)(6)(7) . Although there are international and Brazilian recommendations for the limiting of sodium consumption both for the population in general and for hypertensive individuals of 5g and 4g respectively (8)(9) , studies with different populations show a consumption of sodium which is higher than the recommended (9)(10)(11)(12)(13)(14) , with an average of up to 4600mg of sodium (11.5g of salt)/day (7) . An important study in the area, the INTERSALT (2)(3) , undertaken with 10,079 men and women between 20 and 59 years of age, from 52 centers, aimed at testing hypotheses within and between populations regarding the relationship between 24-hr urinary sodium excretion and levels of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Among the factors related to the development and progression of hypertension, the elevated consumption of salt has been directly associated with the increase in blood pressure levels and the occurrence of cardiovascular complications (2)(3)(4)(5)(6)(7) . Although there are international and Brazilian recommendations for the limiting of sodium consumption both for the population in general and for hypertensive individuals of 5g and 4g respectively (8)(9) , studies with different populations show a consumption of sodium which is higher than the recommended (9)(10)(11)(12)(13)(14) , with an average of up to 4600mg of sodium (11.5g of salt)/day (7) . An important study in the area, the INTERSALT (2)(3) , undertaken with 10,079 men and women between 20 and 59 years of age, from 52 centers, aimed at testing hypotheses within and between populations regarding the relationship between 24-hr urinary sodium excretion and levels of blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A disadvantage of this objective measure is that it reflects one-time food consumption and does not identify the food sources, which is only possible through self-report tools. In addition to validating self-report measures, this study also revealed very high salt intake-about 12 g salt/a day-among the participants, three times greater than the value recommended for hypertensive individuals (19) .…”
Section: The Conceptual Structure and Methodological Designsmentioning
confidence: 69%
“…Evidence found in previously mentioned studies (19)(20) grounded step 1 of the intervention mapping: salt intake is high among hypertensive individuals and the main source of consumption is adding salt while preparing food. A reduction in adding salt is explained in 22% of the cases by motivation (intention to act), which in turn is explained by the constructs of self-efficacy and habit.…”
Section: The Conceptual Structure and Methodological Designsmentioning
confidence: 92%
See 1 more Smart Citation
“…24 In a study in Porto Alegre, in southern Brazil, Micheli and Rosa 25 did not find good agreement between the food register and 12-hour urinary sodium excretion.…”
Section: Discussionmentioning
confidence: 90%